Methodical essay. The development of indicators for the analysis of social precariousness in the AMGR-2010 (Senderos, 2023)
Research about urban inequalities pose a significant academic challenge when aimingat acquiring a better understanding and a more complex outlook on reality. This article seeksto analyze social precariousness in the Metropolitan Area Greater Resistencia (AMGR by itsname in Spanish) for the year 2010. It was thus necessary to develop PrecariousnessIndicators -PI- by considering deficient categories that arise from the different dimensionsproposed by INDEC 2010. Alternatives can be combined in a methodological essay, and theproposed research problem is therefore addressed through two spatial analysis techniques,segregation and spatial aggregation or grouping analysis. It was possible to establish thepredominance of the center-periphery relationship in the distribution of social precariousnessin the AMGR for the year 2010, both in the spatial behavior of segregation and in the resultsobtained from the spatial grouping analysis.
Keywords: Indicators of social precariousness; Segregation; Grouping analysis